Antigen-Specific IFN-γ/IL-17-Co-Producing CD4+ T-Cells are the Determinants for Protective Efficacy of Tuberculosis Subunit Vaccine - Han-Gyu Choi; Kee Woong Kwon; Seunga Choi; Yong Woo Back; Hye-Soo Park; Soon Myung Kang; Eunsol Choi; Sung Jae Shin; Hwa-Jung Kim (Vaccines, 2020)
The antigen-specific Th17 responses in the lungs for improved immunity against Mycobacterium tuberculosis (Mtb) infection are incompletely understood. Tuberculosis (TB) vaccine candidate HSP90-ESAT-6 (E6), given as a Bacillus Calmette-Guérin (BCG)-prime boost regimen, confers superior long-term protection against the hypervirulent Mtb HN878 infection, compared to BCG or BCG-E6. Taking advantage of protective efficacy lead-out, we found that ESAT-6-specific multifunctional CD4+IFN-γ+IL-17+ T-cells optimally correlated with protection level against Mtb infection both pre-and post-challenge. Macrophages treated with the supernatant of re-stimulated lung cells from HSP90-E6-immunised mice significantly restricted Mtb growth, and this phenomenon was abrogated by neutralising anti-IFN-γ and/or anti-IL-17 antibodies. We identified a previously unrecognised role for IFN-γ/IL-17 synergism in linking anti-mycobacterial phagosomal activity to enhance host control against Mtb infection. The implications of our findings highlight the fundamental rationale for why and how Th17 responses are essential in the control of Mtb, and for the development of novel anti-TB subunit vaccines.